Analysis of factors affecting the quality of financial statements of central government institutions: An empirical study in Indonesia - Reschiwati; Simanjuntak, Pahala; Hamilah (Asian Economic and Financial Review, 2025)
This study examines the elements that influence the quality of financial statements within the central government agencies of Indonesia. It highlights the significance of sound governance, accounting practices, skilled human resources, and robust internal audits, with the internal control system serving as a mediating factor. A diverse range of stakeholders participated in the study, including high school graduates, echelon one officials, administrative staff, auditors, accounting and finance professionals, budget and program management officers, and treasurers. Employing purposive sampling, 168 individuals were selected, and data analysis utilized the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results show that the internal control system's performance is affected by a solid accounting system, competent human resources, and a proficient internal audit. Likewise, financial reporting quality is influenced by good governance, the effectiveness of the internal control system, and the efficiency of internal audits. In this context, the internal control system serves as a bridge linking human resources competence to the quality of financial reporting. The study highlights the necessity for policies that foster transparency, maintain confidentiality, adopt standardized accounting practices, enhance human capital, ensure audit independence, broaden internal audit scopes, and strengthen internal control systems.